Faculty awareness of the economic and environmental benefits of augmented reality for sustainability in Saudi Arabian universities. (20th July 2019) - Alahmari, Muteeb; Issa, Tomayess; Issa, Theodora; Nau, S. Zaung
Abstract: In recent decades, smart technology has been one of the major thought-provoking research subjects in the quest to meet the needs of society in ways that do not damage or deplete the environment and that conserve natural resources. Augmented reality is an emerging technology that blends three-dimensional virtual objects with reality. Technologies such as Augmented Reality can be useful tools to promote sustainable development in higher education in terms of various economic, social and environmental considerations. This paper aims to investigate faculty members' awareness of the potential benefits of incorporating Augmented Reality technology in Saudi Arabian universities in terms of its economic and environmental sustainability. For this study, quantitative data was collected by means of a survey questionnaire where participants responded to statements on a five-point Likert scale that ranged from "totally agree" to "totally disagree". The study was conducted with a sample comprising 228 academic and e-learning department staff from Saudi universities. The exploratory factor analysis technique was utilised to identify factors related to awareness of advantages of using Augmented Reality in education, particularly in relation to sustainability. Two factors were identified, namely environmental and economic factors. Study findings indicated that academic and e-learning department staff believe that the use of Augmented Reality in higher education has positional environmental and economic sustainability benefits. The findings from this study provide insights that will assist further studies regarding AR in the Gulf Cooperation Council countries. Graphical abstract: Image 10